Influence of climate on individual tree growth and carbon sequestration in native‐tree plantings. (15th April 2019) - Lada, Hania; Yen, Jian D. L.; Cunningham, Shaun C.; Selwood, Katherine E.; Falcke, Phillip; Hodgson, Jarrod C.; Mac Nally, Ralph
Abstract: Native ecosystems face challenges of past and ongoing human actions, including vegetation clearance and climate change arising from greenhouse gas emissions. Reforestation is an important tool for sequestering carbon, so we sought to determine how replanted native trees responded to weather, soil conditions and planting characteristics. We measured girth growth of 13 tree species in 19 native mixed‐species plantings and one remnant in south‐eastern Australia, bimonthly from 2011 to 2016; replantings ranged between 6 and 46 years at the commencement of measurements. Band dendrometers (flexible bands that record changes in girth) were used to measure growth, with 34 measurements per tree taken over 5 years. We used outcomes from models with several plausible weather future scenarios (Dry, Wet, Wet‐to‐Dry and Average) for 25 and 50 years for tree girth, and 25 years for carbon accumulation, into the future. Woody species richness enhanced girth growth of all tree species. Higher maximum temperatures and reduced rainfall, which generally are predicted for the region over coming decades, retarded growth of nine tree species. Planting tree density had no discernible association with growth for the range of planting densities used. The most and least carbon were sequestered in Wet and Dry projections, respectively. Three Acacia spp. (N‐fixers) grew slowest and would sequester least carbon, while four species of Eucalyptus grew fastest. These measurements of growth provide critical information for land managers to guide choice in replanting strategies for carbon storage.